Combatting anthrax outbreaks across Nigeria's national land borders: need to optimize surveillance with epidemiological surveys - Hammed O. Mogaji; Babatunde Adewale; Stella I. Smith; Ehimario U. Igumbor; Chidumebi J. Idemili; Andrew W. Taylor-Robinson (BMC, 2024)
Abstract Background Anthrax is a non-contagious zoonotic disease caused by the Gram-positive, spore-forming bacterium Bacillus anthracis. Infection is common in livestock and wild animals such as cattle, goats, sheep, camels, and antelopes. In humans, anthrax may occur after contact with contaminated carcasses or animal products like milk and meat. The best method to prevent anthrax in people is to ensure livestock are vaccinated, which significantly limits the risk of zoonotic spread to humans. However, the rate of vaccination of domesticated animals kept by nomadic pastoralists in West Africa is low. These groups regularly cross over national boundaries with their grazing herds. Nigeria is a country that historically has done comparatively well to contain this public health threat. However, in 2023 several outbreaks of human disease appear linked to the consumption of anthrax-contaminated animal products brought into Nigeria by pastoralists from neighboring countries. Clinical manifestations include skin sores or ulcers, nausea, vomiting, and fever. This article aims to raise awareness of recent outbreaks of anthrax in West Africa and to call for a renewed focus on measures to combat this neglected public health concern to the region. Main body The imperative to pinpoint pivotal issues relating to the ongoing emergence of anthrax cases in Nigeria cannot be overstated. By delving into the prevalence of anthrax in both livestock and human populations residing along Nigeria's borders, unraveling the genetic diversity and potential sources of B. anthracis strains, and identifying the primary animal host(s) responsible for transmission, we stand to enhance our understanding of this critical issue. Furthermore, investigating the multifaceted factors contributing to anthrax transmission, assessing community knowledge and practices, mapping common migratory routes of pastoralists, and formulating targeted intervention strategies tailored to the challenges of border communities, are each crucial steps towards effective control and prevention. Conclusion Closing these knowledge gaps on anthrax is not only essential for safeguarding both animal and human health but also for fostering sustainable and resilient communities. Addressing research questions on these interdisciplinary concerns will undoubtedly pave the way for informed decision-making, proactive measures, and a more secure future for Nigeria and its border regions. Graphical Abstract